Foreign capital inflow and its welfare implications in a developing country context - Rudrarup Mukherjee (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
In a small open developing country context, the author considers a three-sector general equilibrium framework and tries to find out the effects of foreign capital inflow on welfare of the country. Comparative-static results show that foreign capital inflow widens the skilled-unskilled wage gap under some reasonable conditions, although it causes an expansion of the foreign enclave and the agricultural sector and contraction of the domestic manufacturing sector. Taking sector specific foreign capital, the authors find that foreign direct investment is beneficial in a free market small open economy in the absence of tariff.
Keywords: D50; D60; F4; F63; O11; 330; foreign capital; small open economy; welfare; tariff; economic development